Post-literacy in Niger: Program design and the transfer of learning - Peter Easton; Laouali Malam Moussa (Adult Education Research Conference, 1996)
Post-literacy programs have been adopted in many countries of West Africa as a means of dealing with the paucity of applications for new literate competence in rural areas and the patch results of adult education. Results of such endeavors in the Republic of Niger provide a good means of analyzing their strengths and weaknesses.